A new genus of caponiid spiders with its phylogenetic placement within Nopinae and the description of a new species of Orthonops Chamberlin, 1924 from Eastern Mexico (Araneae: Synspermiata, Caponiidae) - Galán-Sánchez, M. Antonio; Álvarez-Padilla, Fernando (Zootaxa, 2022)
A new caponiid genus, Aamunops gen. n., is described and its phylogenetic placement within Nopinae tested using a published morphological data matrix. This genus includes four species collected during three standardized inventories in the state of Veracruz, Mexico. All specimens were collected inside plots of oak forests and tropical wet forests fragments, from leaf litter using active searching, sifted litter processed with Berlese funnels and pitfall traps. Aamunops gen. n. was recovered monophyletic under equal and implied weighting schemes including the following species: Aamunops olmeca sp. n., A. chimpa sp. n., A. misi sp. n. and A. noono sp. n. An additional character for females and two new characters states for males were added to the published dataset. In addition, Orthonops confuso sp. n. is described and its phylogenetic affinities discussed. More information regarding these inventories and additional images for the described species can be found online at http://www.unamfcaracnolab.com